The Influence of Brand Satisfaction and Luxury Brand Attachment on Customer Advocacy Through Brand Loyalty on Zalora Marketplace - Michelle Yoanna Franscisca Brigitta; M. Irhas Effendi; Dyah Sugandini; Ignatius Agus Suryono (International Journal of Applied Business and International Management, 2023)
This study is an exploratory study where researchers try to measure the influence of luxury brand fashion objects during the Covid-19 pandemic. The pursose of this research is to produce an overview of the marketing strategy for the online store Zalora Indonesia which sells luxury fashion brands, in an efffort to face very tight competition in the market in Indonesio and to recover after being affected by the Coved-19 pandemic by measuring the magnitude of the influence of brand satisfaction, luxury brand attachment, and brand loyalty on customer advocacy. The respondents in this study were 150 who were customers of luxury fashion brands in Zalora Indonesia who had made a purchase at least once. Non-probablity sampling is the sampling technique, and purposive sampling is the sampling method. The results show that luxury brand attachments have an influence on brand loyalty, and will increase customer advocacy. The practical implication of this research is that Zalora Indonesia, which sells luxury goods, can increase customer advocacy for online purchases through Zalora Indonesia.